2012
DOI: 10.1136/jfprhc-2011-100213
|View full text |Cite
|
Sign up to set email alerts
|

Contraceptive efficacy and tolerability of ethinylestradiol 20 µg/drospirenone 3 mg in a flexible extended regimen: an open-label, multicentre, randomised, controlled study

Abstract: BackgroundThe contraceptive efficacy and tolerability of a new flexible extended regimen of ethinylestradiol (EE) 20 μg/drospirenone (DRSP) 3 mg to extend the menstrual cycle and enable management of intracyclic (breakthrough) bleeding (flexibleMIB) was investigated and the bleeding pattern compared with a conventional 28-day regimen and a fixed extended 124-day regimen.Study designThis Phase III, 2-year, multicentre, open-label study randomly (4:1:1) allocated women (aged 18–35 years) to the following regimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
45
2
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(57 citation statements)
references
References 23 publications
4
45
2
6
Order By: Relevance
“…Наши данные согласуются с результатами круп-ного многоцентрового рандомизированного иссле-дования, проведенного C. Klipping и соавт. [14]. В течение первых 90 дней исследования среднее коли-чество дней кровотечений/мажущих выделений в группе стандартного режима дозирования оказалось 22,6, в группе пролонгированного режима -21,7, при этом мажущие выделения продолжались 8 и 12,7 дня, а кровотечения 14,6 и 9 дней соответственно.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Наши данные согласуются с результатами круп-ного многоцентрового рандомизированного иссле-дования, проведенного C. Klipping и соавт. [14]. В течение первых 90 дней исследования среднее коли-чество дней кровотечений/мажущих выделений в группе стандартного режима дозирования оказалось 22,6, в группе пролонгированного режима -21,7, при этом мажущие выделения продолжались 8 и 12,7 дня, а кровотечения 14,6 и 9 дней соответственно.…”
Section: Discussionunclassified
“…С учетом данных, полу-ченных C. Klipping и соавт. [14], пролонгирование исследования наиболее вероятно привело бы к зна-чимому снижению общего количества дней кровоте-чений/мажущих выделений в группе пролонгиро-ванной терапии, а также к постепенному уменьше-нию длительности «внеплановых» мажущих выделе-ний и кровотечений. Также следует учитывать не-большой размер выборки в нашем исследовании (по 30 больных в каждой группе), его пилотный харак-тер, что может приводить к уменьшению мощности исследования и точности получаемых результатов.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…In this regard, the efficacy and tolerability of a combined OC in a flexible extended regimen has recently been investigated which, when compared with the conventional 28-day regimen, showed significant reductions in the number of bleeding/spotting days and withdrawal bleeding episodes. 21,22 Previous studies have shown that some women worry about the possibility of menstrual "build-up," creation of an "unnatural" state, and the possibility of pregnancy with "missed" monthly bleeding. [6][7][8]20 These misconceptions were also observed in the present survey, in which most women cited health concerns as the main reason for not reducing bleeding frequency, either occasionally or regularly; a large proportion of women also reported that they felt that monthly bleeding was necessary to cleanse the body.…”
Section: Discussionmentioning
confidence: 99%
“…Новый режим приема КОК оказался прост для понимания, большинство жен-щин были довольны данной схемой [19][20][21][22][23].…”
unclassified